A Supplier Selection Model for Textile and Apparel Companies: An Analytic Network Process Approach - Nong, Nhu Mai Thi; Ho, Phong Thanh (ExcelingTech, 2020)
The purpose of this study is to help textile and apparel (TA) companies select their best suppliers by using a suitable Multicriteria Decision Making (MCDM) method. From then, a managerial and theoretical implications are made to adjust the set of criteria to make it more effective and the selection method for TA companies. In order to do that, first, the literature on supplier selection criteria was reviewed to determine necessary criteria for TA industry. Next, an appropriate methodology was proposed to build up a selection model. Then, the proposed approach was implemented in three particular companies in the industry. Finally, discussion on managerial and theoretical aspects of the MCDM and the set of supplier selection was made. The findings will be a good contribution to the selection process of TA companies as they can utilize these criteria to select capable suppliers.